Factors that expose nurses to patient aggression in psychiatric and nonpsychiatric settings – an observational study - Pekurinen, Virve (fi=Turun yliopisto|en=University of Turku|, 2018)
The overall aim of this study is to describe nurses’ individual characteristics and relationship and work environment factors that expose them to patient aggression in psychiatric and non-psychiatric care settings (emergency, and medical and surgical specialties). The Socio-Ecological Model for the prevention of patientto-worker aggression in hospitals was used as a theoretical framework. The setting of this study was made up of the 21 hospitals that were included in the Finnish Public Sector Study. The participants were the nurses who participated in the Finnish Public Sector Study in 2012 and 2015. First, the extent of the problem was described by determining the occurrence, characteristics and consequences of aggression in psychiatric and two non-psychiatric settings by using cross-sectional data from 5228 nurses. Second, cross-sectional approaches were used to identify how nurses’ individual characteristics, relationship and work environment factors were associated with their experiences of patient aggression in psychiatric specialties (758–923 nurses). Third, a longitudinal approach was used to investigate the associations identified in the cross-sectional analysis, in all three nursing groups (2981 nurses). Different types of statistical methods were used to analyze the data, e.g., descriptive statistics, logistic regression and advanced modeling techniques. The results reveal that aggression was experienced by 41% of nurses (N=5228). The most commonly experienced type of aggression was mental abuse, and the rarest type was armed threats. The consequences of aggression in terms of sleep problems and psychological distress may have been more severe in non-psychiatric nursing groups compared to the psychiatric nursing group. Regarding exposing factors, significant associations between nurses’ individual characteristics and patient aggression were identified in the psychiatric, and medical and surgical nursing group, while none were found in the emergency nursing group. In the nonpsychiatric nursing groups, the relationship factor of poor team climate, and the work environment factors of high effort-reward imbalance, high job strain and poor organizational justice at baseline were associated with increased patient aggression at the follow-up. However, these associations differed between the two nonpsychiatric nursing groups. The results of this study show the complex nature of patient aggression in healthcare. Improving nurses’ relationship and work environment factors when aiming to reduce patient aggression may be useful. However, the results of this study indicate that the non-psychiatric care environments may be more vulnerable to patient aggression related to problems at the relationship and work environment levels. More studies are needed to support the findings of the study.